Políticas públicas e a saúde indígena : o atendimento das crianças indígenas no Hospital da Criança Santo Antônio - Gomes, Elianete de Souza (2018)
The theme of this dissertation is indigenous health and public policies related to this context. The understanding of these policies was fundamental to understand the context studied, which is the lack of preparedness of health professionals to deal with the differences between indigenous and non-indigenous peoples. Even though we know that there are national policies that seek to preserve indigenous culture, customs and practices, such as the language and ancestral practices and their particularities, we are faced with many prejudices and lack of knowledge of these policies for a more specific service than at least cultural impacts of indigenous peoples to encounter another culture totally different from those experienced in indigenous communities. In this way, this research analyzed the public policies around health actions directed at indigenous health in the State of Roraima, countering the practices of these public policies aimed at indigenous health in the hospital of the Child Santo Antonio, if they are observed or not. The universe of social relations between the health professionals and the indigenous people that are treated at the referred health unit was explored in order to expand the look to other differentiated and significant contexts, such as the implementation of the Health Policy of Indigenous Peoples and other health policies aimed at this population. The main objective of the research was to analyze the lack of preparation of health professionals to perform a differentiated care for the indigenous people, based on public policies directed to the indigenous people and totally unknown by a large part of these health professionals, the lack of preparation of these in understanding principles and guidelines provided by the Unified Health System and the Subsystem of Attention to Indigenous Health is one of the main points that we analyze in the interviews and questionnaires carried out in this research. We seek answers to the understanding of this theme. Studies of this dimension have become essential for the deeper compression of the relationships between distinct cultures, especially in the context of care in health units, in regard to performing a differentiated care for the indigenous. The result of the research points to a need for health policies aimed at the professionals that serve the indigenous people in health units, so that we get closer to a more humanized and adequate care that meets the needs of the Indians that come from the communities and less prejudiced in the sense of knowing the least about the patient they are in their care.